Amplification of cell signaling and disease resistance by an immunity receptor Ve1Ve2 heterocomplex in plants - Melanie Kalischuk; Boje Müller; Adriana F. Fusaro; Champa P. Wijekoon; Peter M. Waterhouse; Dirk Prüfer; Lawrence Kawchuk (Communications Biology, 2022)
Transgenic plants expressing both Ve1 and Ve2 conferred enhanced signaling and disease resistance in susceptible potato in a race-specific manner, a step forward in generating disease resistant plants against Verticillium.